Development of a bioaffinity SPR immunosensor based on functionalized graphene oxide for the detection of pregnancy-associated plasma protein A2 in human plasma - Chiu NF (Dove Medical Press, 2019)
Nan-Fu Chiu,1 Ming-Jung Tai,1 Hwai-Ping Wu,1 Ting-Li Lin,1 Chen-Yu Chen2,31Laboratory of Nano-photonics and Biosensors, Institute of Electro-Optical Engineering, National Taiwan Normal University, Taipei 11677, Taiwan; 2Department of Obstetrics and Gynecology, Mackay Memorial Hospital, Taipei City 10449, Taiwan; 3Department of Medicine, Mackay Medical College, Taipei 25245, TaiwanCorrespondence: Nan-Fu ChiuLaboratory of Nano-photonics and Biosensors, Institute of Electro-Optical Engineering, National Taiwan Normal University, No. 88, Sec. 4, Ting-Chou Road, Taipei 11677, TaiwanTel +886 27 734 6722Fax +886 28 663 1954Email nfchiu@ntnu.edu.twBackground: Graphene-like material such as functionalized carboxyl-graphene oxide (carboxyl-GO) can be intelligently tuned to achieve particular properties for biological and chemical sensing applications.Methods: In this study, we propose a method to improve interference of non-specific proteins for use in human plasma assays. The highly specific interactions between molecules are an advantage of carboxyl-GO-based surface plasmon resonance (SPR) immunoassays, and this can be applied to spiked plasma samples with pregnancy-associated plasma protein A2 (PAPPA2).Results: The experiment results showed that carboxyl-GO could be used to modulate the plasmon resonance energy, work function and conductivity properties. In addition, carboxyl groups could be used to enhance the conduction of electrons between carboxyl-GO and Au electrodes due to the excellent conductivity and electron transfer rate. The carboxyl-GO-based SPR chip exhibited high sensitivity based on the electric field amplification effects of the composite dielectric material. Therefore, the surface electric field could be enhanced by electron transfer, thereby greatly improving the sensitivity of the sensing system. Enhanced electric field intensity was generated around the carboxyl-GO of 63.58 V/m, and the measured work function was 4.95 eV. The results showed that the carboxyl-GO-based SPR biosensor had high sensitivity, affinity and selective ability for PAPPA2 protein with a high association rate constant (ka) of 3.1 ×109, M-1, S-1, and a limit of detection of 0.01 pg/mL in spiked human plasma.Conclusion: The results showed a detection accuracy of protein in spiked plasma of >90% compared to PBS buffer, suggesting that the carboxyl-GO-based SPR biosensor could be used in assays of human plasma for early and late gynecological diseases. The future of this technology will be useful for the diagnosis and evaluation of the risk of early maternal preeclampsia and potentially in clinical applications for gestational diseases.Keywords: carboxyl, graphene oxide, carboxyl-GO, surface plasmon resonance, SPR, pregnancy, associated plasma protein A2, PAPPA2